State of Monitoring and Supervision in Primary Education at Upazila Level in Bangladesh - Md. Jahangir Alam; A K M Mahmudul Haque; Imran Hossain (UIN Sunan Gunung Djati Bandung, 2023)
Primary Education is a basic education for all, monitored by different agencies at the Upazila level to ensure quality. The researcher aims to explore overall monitoring and supervision scenario in primary Education at the Upazila level to ensure quality primary Education. The study used mixed methods with an explanatory sequential design and mostly qualitative approach. It focuses on Upazila Education Office, and other assigned primary Education related organizations and offices; Charghat of Rajshahi and Sundargonj of Gaibandha had been selected as the study area to observe what they, UEO and AUEO of these areas could do and what they are doing in reality. Through different interviews, questionnaire surveys and document reviews, the researcher has explored the scenario of these offices and officers and made some suggestions to ensure quality primary Education in Bangladesh.